Kajian Kriteria Mutu Air Irigasi - Iskandar A. Yusuf (Balai Teknik Irigasi, 2014)
Government Regulation No. 82 year 2001 regarding Water Quality and Water Pollution Control containing water quality criteria based on water quality classes, so water quality objectives with the wide range utilization become less specific then the quality of the irrigation raw water must meet class II, class III and class IV. On the other hand, the need of water for agricultural irrigation sector is a very large ammount and their needs is getting increase in line with population growth, while the availability of water is on the wane and more aggravated due to the presence of an increasingly severe pollution. Therefore, to meet the needs of large amounts of water with good quality increasingly difficult. It is very burdensome of raw water providers, “what the water quality criteria is needed for irrigation ? “ Based on the analysis of benchmarking several references and then to compose a propose of irrigation water quality criteria. Furthermore, evaluating water quality data of raw water irrigation in Walahar weir of Citarum River-Karawang, Pamarayan weir of Ciujung River-Serang and irrigation canal in Garang River Semarang. Based on the propose of water irrigation criteria resulted in good and very good classification, however, based on class II of water quality criteria resulted not suitable classification, however, it has good productivity that higher then the national average productivity. Indeed, the water quality criteria of Government Regulation No. 82 year 2001 is still prevailed for water quality standards determination and water quality objective standards is set up by other relevant regulations such as: Regulation of Government/Governor/Mayor based on their obligation.